Image compression using Analytical and Learned Dictionaries - Padma Priyanka, Gaddam; Geetha Priya, Mosali; Harshali, M; Venu Gopala Rao, M (International Journal of Engineering and Technology, 2018)
The modern signal and image processing deals with large data such as images and this data deals with complex statistics and high dimensionality. Sparsity is one powerful tool used signal and image processing applications. The mainly used applications are compression and denoising. A dictionary contains information of the signals in the form of coefficients. Recently dictionary learning has emerged for efficient representation of signals. In this paper we study the image compression using both analytical and learned dictionaries. The results show that the effectiveness of learned dictionaries in the application of image compression.Â Â